Total Esophagogastric Dissociation for Refractory Gastroesophageal Reflux Disease: Preliminary Experience - PD, D´Alessandro; MA, Rubio; EGN, Paz; SC, Takeda; MM, Boglione; ME, Barrenechea (Archives of Clinical and Biomedical Research, 2026)
Background: Neurologically impaired (NI) children frequently present with severe swallowing difficulties and gastroesophageal reflux disease (GERD), leading to recurrent aspiration and failure to thrive. While Nissen fundoplication is the standard treatment, it carries a high risk of recurrence in this population due to gastric dysmotility and spasticity. Total esophagogastric dissociation (TEGD) is a definitive surgical alternative for redo cases or primary treatment in selected patients where anti-reflux failure significantly impacts quality of life. Aims: To describe our initial institutional experience with TEGD, reporting surgical outcomes, early and late complications, and preliminary qualitative observations regarding postoperative quality of life in a complex pediatric cohort. Methods: A retrospective observational review was conducted using an institutional REDCap database (2007–2023). All patients undergoing TEGD were included without exclusion criteria. Data on demographics, primary diagnosis, surgical history, and complications were analyzed. Postoperative quality of life was assessed through structured caregiver interviews focused on respiratory events, vomiting, and feeding habits. Due to the small sample size, a descriptive analysis was performed to avoid Type II statistical errors. Results: Eighteen children (11 male, 7 female) underwent TEGD, with 66.7% presenting severe neurological impairment. Six procedures were primary and twelve were secondary "rescue" cases. Early complications (within 30 days) occurred in 33.3% of patients (n=6), with 83% requiring surgical revision for issues such as bowel obstruction or anastomotic leakage. Late complications affected 16.6% (n=3), all requiring surgery. The overall mortality rate was 11% (n=2), with only one death directly related to a late surgical complication (small bowel volvulus). Despite the morbidity, all caregivers reported an improvement in quality of life due to the resolution of GERD and a reduction in major respiratory events and vomiting. Improvements in feeding efficiency and weight gain were also consistently noted. Conclusion: TEGD provides a definitive anatomical barrier against reflux in complex pediatric patients when traditional methods fail. Although associated with a significant complication rate and a demanding learning curve, it offers high clinical success and improved well-being for NI children. Comprehensive preoperative counseling is essential for families considering this procedure.